2005
DOI: 10.1177/014556130508400413
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma of the Internal Auditory Meatus: A Rare Occurrence in the Internal Auditory Canal

Abstract: We describe a cas e of angioleiomyoma of the internal auditory meatu s. Afinding ofthis tum or at this site is ve,y unusual. In fa ct, our review ofthe literature revealed that only 1 case has been previously reported. 1n our patient, the tumor was clinically and radiologically difficult to distingu ish frotn an acoustic neuroma. It would be important to recognize this rare small tumor preoperatively because it may be appropriate to manage it conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Gasco et al [ 10 ] reported a large ALM originated from the transverse sinus. A few cases reported small nodules on the dura [ 6 , 11 , 13 ], and a peculiar case in auditory meatus [ 9 ]. Some ALMs occur on cranial bone, with the majority were in the facial bones such as the mandible and maxilla [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gasco et al [ 10 ] reported a large ALM originated from the transverse sinus. A few cases reported small nodules on the dura [ 6 , 11 , 13 ], and a peculiar case in auditory meatus [ 9 ]. Some ALMs occur on cranial bone, with the majority were in the facial bones such as the mandible and maxilla [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1994 Lach et al 10 described the first primary intracra nial angioleiomyoma, in an extraaxial location (leptom eningeal). To the present time, 4 additional intracranial cases have been documented; 4,7,8,14 of these, only the case reported by Ravikumar et al 14 was intraaxial (basal gan glia). Karagama et al 7 and Kohan et al 8 have verified le sions in the IAM.…”
Section: Discussionmentioning
confidence: 73%
“…To the present time, 4 additional intracranial cases have been documented; 4,7,8,14 of these, only the case reported by Ravikumar et al 14 was intraaxial (basal gan glia). Karagama et al 7 and Kohan et al 8 have verified le sions in the IAM. Figueiredo et al 4 have described a lesion in the cavernous sinus.…”
Section: Discussionmentioning
confidence: 73%
“…►Tables 1, 2, and 3 summarize the clinical, radiologic, surgical, and pathologic findings in all previous reports about intracranial ALMs including our case. [1][2][3][5][6][7][8][9][10][11][12][13] The data reviewed here show that intracranial ALMs were more frequently found in men (9 cases: men, 3 cases: women; 1 case: unknown) than in women in contrast to extremity ALMs ( Table 1). The average age was 43.5 years (standard deviation [SD]:16).…”
Section: Discussionmentioning
confidence: 98%